Tupelo Medical : managing price erosion - Anderson, Eric T.; Abraham, Daniel; Anderson, Elizabeth; Santaella, Gus ([London] : SAGE, 2016)
Robert Davidson, pricing manager for Tupelo Medical, was concerned about the variability in price paid for its top-selling product, the Micron 8 Series blood pressure monitoring system. Using historical transaction data, this case explains how Davidson determines the appropriate price floor for the system.
Originally Published in: Anderson, E. T, Abraham, D., Anderson, E. L, & Santaella, G. (2013). Tupelo Medical: Managing Price Erosion. 5-412-750. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Medical instruments and apparatus industry -- Case studies; Industrial marketing -- Case studies; Pricing -- Case studies